Diagnosis and Treatment of Osteoporosis in High-Risk Patients Prior to Hip Fracture - Gleason, Lauren J. (SAGE Publications, 2012)
PURPOSE: Hip fractures in older adults are common and serious events. Patients who sustain fragility hip fractures are defined as having osteoporosis. Patients with dementia or a history of a prior fragility fracture are at increased risk of a future fracture. This study assesses prefracture osteoporosis diagnosis and treatment in high-risk groups. METHODS: A case–control analysis of a database of all patients age ≥60 years admitted for surgical repair of nonpathological, low-impact femur fracture between May 2005 and October 2010 was performed. RESULTS: Of 1070 patients, 511 (47.8%) had dementia and 435 (40.7%) had been diagnosed with osteoporosis prior to admission. Patients with dementia were more likely to have a diagnosis of osteoporosis prior to their fracture than those without dementia (43.8% vs 37.7%, P < .05). Twenty-five percent of the total study population had been treated with calcium and vitamin D (Cal+D) prior to admission, and 12% with other osteoporosis medications. There was a trend toward patients with dementia being more likely to have been on Cal+D prior to admission (27.6% vs 22.5%, P = .06), but no difference in treatment with other agents (10.8% vs 13.1%, P = .25). Patients with prior fragility fractures were more likely to be on Cal+D (32.3% vs 25.0%, P < .02); however, there was no difference in the use of other osteoporosis medications (12.3% vs 12%, P = .90). CONCLUSION: Fewer than half of patients that presented with hip fractures were diagnosed with osteoporosis prior to fracture and primary preventative treatment rates were low. Although patients with dementia are more likely to be diagnosed with osteoporosis, they were not more likely to be treated, despite having a greater risk. Additionally, those with prior fragility fractures are often not on preventative treatment. This may represent a missed opportunity for prevention and room for improvement in order to reduce osteoporotic hip fractures.